ANALISIS KEBUTUHAN SARANA DAN PRASARANA PENDIDIKAN ISLAM DI PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA - Awaliah, Fuji; Dwi Ratnasari; Otisia Arinindyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Improving the quality of education is an integral part of national development. Education hopes that education in facilities and infrastructure will develop, research on analyzing the needs of Islamic education facilities and infrastructure in private PTKIS is important to find out the shortcomings and needs that exist. This research uses a constructivist paradigm with a descriptive qualitative approach with a type of library research. Regarding data sources, researchers use two types of data, primary data sources, and secondary data. The need for funds for higher education in private universities is carried out for the purpose of collecting data on assistance received by universities and the suitability of using existing assistance or grants in educational facilities and infrastructure in universities and one of the private universities in West Java, precisely in Depok, receives scholarships for students who need assistance from these scholarships. Students who have registered and received scholarships from facilities and infrastructure carried out by the Ministry of Religious Affairs (Ministry of Religion) in the general directorate of Islamic Education. carrying out its duties as an Islamic educational institution, private Islamic religious colleges need to pay attention to the need for adequate facilities and infrastructure. Educational facilities such as classrooms, libraries, laboratories, dormitories, and sports facilities will help students in supporting learning and campus life. Islamic education in private Islamic religious universities can make a significant contribution to the formation of a noble and quality young generation.